Microspatial distribution of trace elements in feline dental hard tissues: early life exposure to essential and toxic elements - Wright, Alexandra L.; Fiani, Nadine; Peralta, Santiago; Arora, Manish; Austin, Christine (Frontiers in Veterinary Science, 2023)
Trace elements play a key role in dental tissue development, as dental hard tissues accumulate essential and toxic trace elements during mineralization. Characterization of the spatial accumulation pattern of trace elements may provide insight into exposure to toxic elements over time and to the nature of disease processes affecting the hard dental tissues. Here, we present the first report of the use of laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) to map the microspatial distribution of multiple trace elements, essential and toxic, across feline enamel, dentin, and cementum using 11 teeth extracted from 8 cats. Nine teeth were from 7 cats diagnosed with idiopathic tooth resorption on intraoral radiographs prior to extraction. Two teeth were included from a cadaver that had no signs of tooth resorption on intraoral radiographs. The normal dental tissue was analyzed from each sample. Results showed a higher accumulation of barium and strontium in coronal dentin as compared to root dentin. The timing of the accumulation mirrors nursing timelines seen in human and non-human primate teeth and is consistent with barium and strontium being sourced from maternal milk. Results also showed a higher uptake of lead in the coronal dentin, suggesting this lead exposure was likely passed from mother to offspring. This work characterizes a baseline for elemental distribution linked to early life exposure to toxic elements such as lead and provides a framework for future studies investigating long-term environmental exposures to trace elements, essential and toxic, and their involvement in feline systemic and dental diseases.